Metabolic mechanisms in heart failure. - Ashrafian, H; Frenneaux, M; Opie, L (2007)
Although neurohumoral antagonism has successfully reduced heart failure morbidity and mortality, the residual disability and death rate remains unacceptably high. Though abnormalities of myocardial metabolism are associated with heart failure, recent data suggest that heart failure may itself promote metabolic changes such as insulin resistance, in part through neurohumoral activation. A detrimental self-perpetuating cycle (heart failure --> altered metabolism --> heart failure) that promotes the progression of heart failure may thus be postulated. Accordingly, we review the cellular mechanisms and pathophysiology of altered metabolism and insulin resistance in heart failure. It is hypothesized that the ensuing detrimental myocardial energetic perturbations result from neurohumoral activation, increased adverse free fatty acid metabolism, decreased protective glucose metabolism, and in some cases insulin resistance. The result is depletion of myocardial ATP, phosphocreatine, and creatine kinase with decreased efficiency of mechanical work. On the basis of the mechanisms outlined, appropriate therapies to mitigate aberrant metabolism include intense neurohumoral antagonism, limitation of diuretics, correction of hypokalemia, exercise, and diet. We also discuss more novel mechanistic-based therapies to ameliorate metabolism and insulin resistance in heart failure. For example, metabolic modulators may optimize myocardial substrate utilization to improve cardiac function and exercise performance beyond standard care. The ultimate success of metabolic-based therapy will be manifest by its capacity further to lessen the residual mortality in heart failure.